Analisis Komunikasi Kelompok dalam Upaya Menjaga Citra PT IPC Terminal Petikemas - Tazkia, Nawa; Pamungkas, Indra Novianto Adibayu; Pramesthi, Jasmine Alya (JOM, 2024)
The implementation of good corporate communication within a groupthink is useful for maintaining the company's image. The assumption of perceived division differences among department members indicates the formation of groupthink. This research aims to understand the decision-making process through groupthink conducted by the Corporate Secretary & External Relations Department of PT IPC Terminal Petikemas and to identify the management and corporate communication strategies in maintaining the company's positive image. This research use a qualitative method, conducting semi-structured interviews with six informants. The results show that the factors contributing to groupthink in the Corporate Secretary & External Relations Department of PT IPC Terminal Petikemas include group stress which comes from external factors that trigger increased internal pressure within the team. The department head functions plays a crucial role in enhancing team performance, ensuring that the decision-making process within the department for maintaining the company’s image is always conducted democratically.